"We are all thrown into one basket": Dyslexia, schools and the (non)enactment of policies of inclusion - Nevill, Thom Paul; Forsey, Martin (Disability Studies Quarterly, 2022)
Since the mid-1990s it has been illegal for Australian education providers to deny students with disabilities the right to access and participate in education. Conjointly, policies and standards have been introduced that devolve the responsibility of ensuring disabled students are able to fully engage in their education to schools. Despite recent studies suggesting dyslexic student needs are rarely met in the Australian school system, to date, little research has examined how developments in anti-discriminatory and inclusive policy affect the provision of support to these students. This paper examines how devolved approaches to inclusive education policy practice affect the lived experiences of dyslexic students in Western Australian schools. Focusing on two young people's stories about their time in school, it is argued that the adoption of devolved approaches to policy has been instrumental in shifting responsibility for the delivery of equitable education for students with learning disabilities to families, and especially mothers. Drawing on a social-relational model of disability and Bourdieusien theories of capital, this paper illustrates how shifting responsibility for inclusion to parents results in inequity. The findings illuminate a need to think more critically about exactly who should be responsible for inclusion.